Determinants of tea planters’ purchasing behavior of planting insurance: SEM analysis - Zhenhua Xu; Nuttawut Rojniruttikul (PLoS ONE, 2025)
This study explores the influence of government support and risk cognition on tea planters’ purchasing behavior regarding planting insurance, with a particular emphasis on the mediating roles of perceived value and environmental concern. Data were collected from 550 tea planters in Guizhou Province, China, using a structured questionnaire and convenience sampling method. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were conducted using AMOS 28.0 to analyze the data. The results indicate that both government support and risk cognition significantly and positively impact the perceived value of planting insurance. To promote the uptake of planting insurance among tea farmers, government agencies should strengthen policy advocacy and provide business guidance. Such efforts would help tea farmers recognize the value and psychological significance of planting insurance, thereby better safeguarding their agricultural interests. This study enhances the understanding of how government support and risk cognition can facilitate the adoption of planting insurance among tea farmers.